Exploring behavioural differences between certificate achievers and explorers in MOOCs. Issue 4 (2nd October 2022) - Liu, Bowen; Wu, Yonghe; Xing, Wanli; Cheng, Gexing; Guo, Shengnan
ABSTRACT: Massive open online courses (MOOCs) face the ongoing problem of low pass rates. A number of MOOC learners engage in most or all course activities but fail to pass the course. To improve participation and thereby increase successful completion, this study explores the behavioural differences between certificate achievers and explorers that lead to their different learning outcomes. Eleven behaviours were extracted from more than 80, 000 behaviour records for 215 certificate achievers and 456 explorers, which were categorized into four types of activities: graded assessment, content-related, course-related, and interactive activities. Random forest classifier, independent-sample t-testing, and lag sequential analysis were used. The results showed six important behaviours that are highly related to certificate achievement. Certificate achievers engaged in more course-related and graded assessment activities during the course, while explorers engaged in more content-related and interactive activities, and graded assessment activities occurring at the end of the course. Compared to explorers, certificate achievers exhibited more bidirectional behaviours in terms of interactive and course-related activities and more repeated behaviours in terms of course-related and graded assessment activities. The study has significant implications for MOOC learners and instructors in improving learning and teaching performance by implementing appropriate behavioural interventions.